Fragment-aided recognition of images under poor lighting and additive impulse noises - Kalashnikov, Vyacheslav V.; Avramenko, Viktor V.; Demianenko, Volodymyr N.; Kalashnykova, Nataliya I. (Elsevier, 2019)
On the base of the first-order integral disproportion functions, two algorithms recognizing fragments of standard images are proposed. Due to the disproportion functions techniques, the algorithms have special advantages when processing poorly lighted images, as well as with signals transmitted in the presence of additive impulse noises.